Exploring the Interplay: Tax Compliance, Financial Reporting Quality, and Auditor Competence - a Survey - Based Analysis - Pangaribuan, Hisar; Sunarsi, Denok; Sihombing, Jenny; Saddam, Muhammad (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study investigates the impacts of auditor competence (AC) and auditor experience (AE) on tax compliance (TC) and financial reporting quality (FRQ). Employing a quantitative research methodology, the study collected data from 67 auditors in Jakarta using purposive random sampling. These auditors, with a minimum of one year of experience, responded to a structured questionnaire distributed via email and WhatsApp. The data analysis was conducted using Smart-PLS to evaluate relationships between AC, AE, TC, and FRQ. Findings revealed that AC significantly enhances both TC and the FRQ. AE also positively influences these outcomes, albeit its hypothesized role as a moderator in the relationship between AC and the auditing outcomes did not show significant effects. These results underline the importance of both AC and AE in achieving high standards in audits but suggest that the interaction between these factors is complex. The study emphasizes the need for targeted professional development that enhances both the depth of competence and the strategic application of experience. It highlights the importance of creating training programs that address specific skills and knowledge areas relevant to improving audit quality and compliance.